Strengthening Police Conflict Management Strategies for Effective Public Safety Governance - Abror Alkindi (Jurnal Scientia Indonesia, 2025)
Effective conflict management within policing is essential to maintaining public order, promoting peaceful dispute resolution, and strengthening community trust. This study examines the role of police conflict-management strategies through an integrated analysis of negotiation approaches, de-escalation techniques, multi-stakeholder cooperation, and early intervention mechanisms. Using a mixed-methods design, five years of operational data from three metropolitan jurisdictions were evaluated alongside interviews with 48 police officers, mediators, and community leaders. Statistical assessment indicates that police units employing structured conflict-management training saw a 31% reduction in violent confrontations and a 22% increase in voluntary compliance during high-tension encounters. Qualitative findings highlight the importance of communication competence, cultural awareness, and emotional regulation in preventing escalation. Yet challenges remain, including inconsistent training standards, limited community involvement, and institutional resistance to procedural reforms. This study concludes that robust, evidence-based conflict-management strategies improve police effectiveness, enhance public trust, and support long-term social stability. The research contributes to police science by offering a comprehensive framework of conflict-management practices and identifying policy recommendations for sustainable implementation.